Dispersal decisions and personality in a freshwater fish. (November 2019) - Coates, William D.; Hale, Robin; Morrongiello, John R.
Abstract : Historically, the differences in dispersal behaviour between individuals within a species has largely been ignored. Instead, we tend to assume all individuals within a population express similar phenotypes. However, evidence is growing for the importance of intraspecific variability in dispersal propensity and how this variability may influence population dynamics, as well as the role of environmental context in driving this behaviour. Individuals that are more likely to disperse can have other traits, such as being bolder or more aggressive, that collectively form behavioural syndromes. We tested for a behavioural syndrome in carp gudgeons ( Hypseleotris spp.) species' complex, a type of small fish found in intermittent streams in southeastern Australia. Intermittent streams are an environment where selection may favour the evolution of different dispersal phenotypes, given the variable and unpredictable nature of flows. During dry periods, fish become isolated in refuge pools that vary in quality and persistence, and then can disperse when flow resumes. Dispersal can have costs (e.g. the risk of not finding another habitat) but also benefits (e.g. opportunity to find better habitat), meaning that different strategies (i.e. dispersing versus staying) may both be advantageous and thus evolve. Through a series of experiments that assessed these fish's latency to emergence into a novel environment and tendency to shoal, as well as movement behaviour in artificial streams, we found that (1) flow is not likely to be a movement cue, and (2) boldness, sociability and dispersal distance were repeatable, consistent with the notion that carp gudgeons exhibit personalities. To our knowledge, this is the first demonstration of a behavioural syndrome in a freshwater fish that inhabits intermittent streams. This finding contributes to our understanding of how carp gudgeons move through intermittent streams and the potential dynamics that allow these fish to persist in such harsh, hydrologically variable habitats. Highlights: We investigate if carp gudgeons from intermittent streams have dispersal syndromes. Carp gudgeons did not use flow as a movement cue. Boldness, sociability and movement distance were repeatable. Our results are consistent with the notion that carp gudgeons exhibit personalities.